ESTUDIO COMPARATIVO DE TRES INDICES DE MALOCLUSIONES OMS, AIO, AGUILA EN UN GRUPO DE ESCOLARES DE 11 A 16 AÑOS DE EDAD DE SEXO FEMENINO EN LA CIUDAD DE LIMA - Menéndez M., Leoncio (1999)
This research consisted in analysis of tree index of maloclussión in spoken in spanich language: a) Index anomalies of dentofaicald of Health Organization of Word, (1979), b) Index of maloclussions od Association of beroamericana of orthodontics, (1987) and c) the Aguila´s index of priority of tratment orthodontics (1992). The sample were one hundred gilrs about 12 to 16 years old. The results of present study are significants, and have to cuestions the tree index for the following razons: 1) because for the applications for many index for diferents poblacions to began diferents, that are imcompatibels for comprations itself. 2)because lo loss infonnmation value and, tóo los the tieme to do diferents typs of index, and, 3) because the OMS index has a defects to valorations of need to treatment and it is subjet and no cuantitative. However. the results of this study are significans for the following dates: Betwing 12 lo 15 years old the 51% to follow crowing 2 to 1Omm, overjet to come 82% to O from 9 mm, overbite to follow 98% from 3/3 of the face of the teeth, the need to treatment of orthodontics to come 83% (Aguila), 60% (AIO) y, 44% (OMS).